2021
DOI: 10.1038/s41598-021-93372-9
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban concentration variability and relation to clinical outcomes in real-life patients with atrial fibrillation

Abstract: In some clinical situations, measurements of anticoagulant effect of apixaban may be needed. We investigated the inter- and intra-individual apixaban variability in patients with atrial fibrillation and correlated these results with clinical outcome. We included 62 patients receiving either 5 mg (A5, n = 32) or 2.5 mg (A2.5, n = 30) apixaban twice-daily. We collected three trough and three peak blood samples 6–8 weeks apart. Apixaban concentration was measured by liquid chromatography-tandem mass-spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…A previous study reported that the median values of C trough and C peak were approximately 25–30% lower in the reduced-dose group than in the standard-dose group [ 7 ]. Similar to the previous real-life studies, the results showed a 25–35% difference in C trough and C peak between the standard- and reduced-dose groups [ 9 , 12 , 20 ]. The results for the reduced-dose group presented a pharmacokinetic alteration, but the clinical outcomes were consistent in terms of efficacy and safety [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A previous study reported that the median values of C trough and C peak were approximately 25–30% lower in the reduced-dose group than in the standard-dose group [ 7 ]. Similar to the previous real-life studies, the results showed a 25–35% difference in C trough and C peak between the standard- and reduced-dose groups [ 9 , 12 , 20 ]. The results for the reduced-dose group presented a pharmacokinetic alteration, but the clinical outcomes were consistent in terms of efficacy and safety [ 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…A history of stroke events and age ≥ 75 years were major risk factors for stroke events in AF patients [ 31 ]. As mentioned above, it may be that the apixaban plasma levels cannot be used to predict stroke outcomes, as suggested by the previous report [ 12 ]. In addition, a cohort study previously reported that thrombotic complications occurred in AF patients who had depleted apixaban plasma levels (22–145 µ/L) and high CHA 2 DS 2 VASc scores [ 32 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The variation of apixaban or rivaroxaban plasma levels in real-world populations has been studied before in patients with nonvalvular atrial fibrillation (NVAF) [ 23 , 24 , 25 , 26 ] or in populations receiving these DOACs for different indications, including management of VTE [ 27 , 28 , 29 ]. Consistent with our results in VTE patients, Testa et al [ 23 ] found an inter-patient CV of up to 42% at peak and up to 68% at trough levels of apixaban 5 or 2.5 mg BD and of up to 49% at peak and 103% at trough levels of rivaroxaban 20 mg OD in patients with NVAF.…”
Section: Discussionmentioning
confidence: 99%
“…For patients taking apixaban 5 mg twice daily, peak plasma concentrations range between 128–488 ng/ml [ 26 , 27 ]. The low plasma concentrations measured in our study, even in animals taking 15 mg twice daily, suggest that oral absorption is limited or that pigs metabolize apixaban rapidly.…”
Section: Discussionmentioning
confidence: 99%